HUELLAS - José Francisco García Sánchez (European Scientific Journal, ESJ, 2014)
Traces are an omen and a premonition. We said we were not the first. They anticipate the species and life. Their presence holds security —and anxiety— granting discover a place already visited. A trace, a sign or a groove aspire to be a secret depositories are required to share. In the traces, resides active memory of a place; and somehow, announce their future, becoming stable and recognizable symbols on the landscape. Sometimes the traces are physical and visual, sound or smell also; sometimes they are invisible. But it is always possible to identify with a symbol, which means the architecture itself and accomplish what should evoke.